Russia's oil & gas sector in global energy transition - Heli Simola; Laura Solanko (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
The past two decades have witnessed a major transformation of global energy markets. While growth in energy demand now comes from emerging economies, and technologies critical to oil and natural gas production have seen dramatic advances, the biggest changes in global energy markets lie ahead. For countries to meet their ambitious climate goals, demand for conventional energy sources must fall significantly and be accompanied by a massive shift in investment to renewable energy sources. Such changes can have major implications for the Russian economy, which depends heavily on oil and gas. This brief provides an overview of the latest trends in Russia's oil & gas sector in the context of evolving global energy markets.
urn:nbn:fi:bof-202105251245
Keywords: 330; Russia; oil; natural gas; energy transition